ANALISIS NILAI TAMBAH BAWANG MERAH LOKAL PALU MENJADI BAWANG GORENG DI KOTA PALU - WN, Dewi Cahyanti; Kassa, Saharia; Howara, Dafina (AGROTEKBIS, 2013)
The role of agroindustryÂ  to maintain the primary product into processing products to increase the added value is required. One of the solutions made is to increase the added value of local Palu onion become fried onions. This study aims to determine the added value of being processing the local Palu onion into fried onion which was conducted on Triple C Fried Onion Industry, Raja Bawang Fried Onion Industry and SAL-HAN Fried Onion Industry. The samples determined by intentionally (purposive), considering that these 3 industries categorized as home industry, small industry and middle industry. Respondents in this study was the leadership and employees of the company with a number of respondents as many as 11 people. The results showed that the added value obtained from fried Onion Industry at home level (Triple C fried onions Industry) of Rp.33.846.09 kg , small scale (Raja Bawang Fried Onion Industry) of Rp .39.117,40/kg and middle scale (SAL-HA Fried Onion Industry) of Rp.39.760/kg